Implementation of a media-based citizen science project learning model using a scientific approach in Civic Education to enhance student critical thinking skills - Momo, Abd Halim; Saleh, Muhamad; Iru, La; Syahbudin, Syahbudin; Salimin, Salimin; Irawaty, Irawaty; Reni, Wa Ode; Nerlin, Nerlin; Piara, Muhrajan (Universitas Negeri Yogyakarta, 2024)
Pancasila and Citizenship Education (PCE) are crucial for developing active, critical, and responsible citizens. Critical thinking is a key competency students should acquire through PCE. This study aims to analyse and evaluate the effectiveness of the Project Citizen learning model utilising a Scientific Approach in enhancing students' critical thinking skills. The long-term objective is to provide junior high school teachers with examples of innovative learning models applicable to all subjects and recommend to relevant agencies to implement the Project Citizen model in PCE to boost critical thinking abilities. This research focuses on creating effective learning models and frameworks for instilling character values in schools. Using a quantitative quasi-experimental design, the study's population consists of all Public Junior High School 3 Kendari students, with a sample drawn from two eighth-grade classes. Data collection involved attitude scale questionnaires, observations, and interviews. Statistical methods were used for quantitative data analysis, while qualitative data were analysed descriptively. The analysis included normality tests, homogeneity tests, comparisons of means, and calculations of normalised gains. Hypothesis testing revealed a significant difference in the effectiveness of the Project Citizen model based on the Scientific Approach compared to conventional teaching methods in improving critical thinking skills at Public Junior High School 3 Kendari.